Servqual Analysis of PT Dago Wisata Umroh Service - Yuska, Novrisky; Chaldun, Evy Rachmawati (Journal of Innovation, Business and Entrepreneurship, 2017)
Abstract. Nowadays, intention of Muslim in Indonesia to perform umrah is increased. This opportunity captured by umrah travel agency in Indonesia, especially Dago Wisata. Dago Wisata provide umrah service for Muslim. It is needed to know customer opinion about Dago Wisata umrah service. The main objective of this research is to know Dago Wisata umrah service quality. This research result also will be applied in Smeva Holiday, company which also focuses in umrah service. This research was using questionnaire and conducted in Bandung with 100 respondents. The SERVQUAL dimensions with the five points of likert scale used in the questionnaire.Â Data will be analyze by using Microsoft excel and SPSS. Importance performance analysis will use in assessing existing service of Dago Wisata and analyzing improvement that need to do by Dago wisata Management to create customer satisfaction.The result show that there three kind of service attribute should improve by Dago Wisata. There is distance between hotel and mosque in Mecca and Medina, closer is better. Dago Wisata should improve employee careness to customer complaints.Â Keywords: Umrah business, SERVQUAL, Importance Performance Analysis